Ricoeur's personalist Republicanism - Deweer, Dries (Lexington Books, 2017)
The political philosophy of personalism – The young Ricoeur's personalism – When personalism dies, the person returns – Ricoeur's personalist political philosophy: continuity and relevance
Includes bibliographical references and index
Keywords: Ricœur; Paul; Personalism; Individualism; Political science; Republicanism